Labirintogoria (ou sobre a experiência : apreender pela arte, fratura entre códigos para um transbordamento dos contornos) - Velho, Ângela Teresinha Fontana de Souza Tambara (2015)
This paper seeks to develop a dialogue between Education, Philosophy and Arts through the thoughts of Stoics, Jacques Derrida, Gilles Deleuze and Anne Cauquelin, among others, which are based on the philosophy of difference and the theory of the incorporeal. It aims to discuss learning, or rather, experience. It seeks to understand the moment that may raise our understanding and development of something that is familiar. It is a reflection on the power of the event, the argumentative value of the artwork, the capacity of knowledge/experience/learning in the movement of the incorporeal according to ancient Stoicism, mobilizing the concept of Labirintogoria. It is not to be affected alone, but by a process of preparation and its continuum.